Lawyers' Earnings in the Canadian Private and Public Sectors - Stager, David (Relations industrielles / Industrial Relations, 1988)
Earnings of lawyers in the government service are compared with those in private practice in Canada during the 1970's, a period of rapid growth in the supply of lawyers.